2023
DOI: 10.3390/foods12142702
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Functional Acceptable Diabetic and Plant-Based Snack Bar Using Mushroom (Coprinus comatus) Powder

Abstract: Consumers’ growing concern about health and well-being has led to increased interest in functional foods. This research aims to evaluate the physicochemical and antioxidant properties of a functional plant-based (PB) snack bar enriched with Coprinus comatus powder. The snack bar formulations exhibited a wide range of flavor and textural characteristics. Two PB snack bars and four commercial bars were evaluated by a consumer panel of healthy volunteers (n = 20). The PB snack bar scored ‘like extremely’ on the 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…The content of fibres in our snack-bars is between 5.4 g/100 g and 6.9 g/100 g; values found in the specific range of other snack bars are between 1 and 20.8% [27,28]. Numerous studies highlight that fibres play a significant role in preventing cardiovascular disease, diabetes, and obesity [30].…”
Section: Nutritional Assessmentmentioning
confidence: 60%
See 2 more Smart Citations
“…The content of fibres in our snack-bars is between 5.4 g/100 g and 6.9 g/100 g; values found in the specific range of other snack bars are between 1 and 20.8% [27,28]. Numerous studies highlight that fibres play a significant role in preventing cardiovascular disease, diabetes, and obesity [30].…”
Section: Nutritional Assessmentmentioning
confidence: 60%
“…Several studies have highlighted a positive relationship between the consumption of one serving (28 g) of nuts daily, and the decrease in the risk of CVD by 21% and mortality from any cause by 22% [29]. In another study, a reduction of up to 27% in the risk of diabetes was revealed in people who consumed at least 5 portions of nuts per week [28].…”
Section: Nutritional Assessmentmentioning
confidence: 99%
See 1 more Smart Citation